Keterkaitan Teks Proposal Bahasa Indonesia Dengan Keterampilan Penyusunan Proposal Bisnis Mahasiswa Akuntansi: Penelitian - T. K. A. Br Purba; S. Ramadhani; S. F. A. Sitorus; A. V. D. Simbolon; R. R. P. Nasution; R. Situmorang; M. A. J. Daulay (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to analyze the relationship between proposal texts in Indonesian language courses and accounting students’ business proposal writing skills. The research applied a qualitative descriptive method, collecting data through observation, literature review, and analysis of student proposals. The findings revealed that mastery of proposal text structure in Indonesian significantly influenced the quality of business proposals prepared by students. Those who understood linguistic rules, writing systematics, and logical argumentation were able to produce business proposals that were more systematic, persuasive, and feasible. In addition, students with better mastery of academic writing skills demonstrated stronger critical thinking and creativity in formulating business ideas. These results confirm that academic Indonesian language proficiency serves as a crucial foundation for developing entrepreneurial competencies, ensuring that accounting graduates are not only competent in theory but also prepared to compete in real business practices.